THE POLITICAL COMMUNICATION STRATEGY OF SUSILO BAMBANG YUDHOYONO IN CONSTRUCTING A CHARISMATIC IMAGE AS A NATIONAL LEADER - Faiz Ahmad Zidan; Ahmad Sampurna Rambe; Muhammad Alfazar; Nursamsiah Pasya; Zulfan Affandi; Muhammad Panusunan Harahap (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study explores the charismatic leadership of Susilo Bambang Yudhoyono (SBY) in the context of political communication, highlighting his assertive, structured, meaningful, and charismatic communication style that defined his presidency in the Republic of Indonesia. Using a qualitative method with a literature study approach, this research analyzes how SBY’s military and academic background shaped his formal yet emotional communication character and his ability to foster a close relationship with the public through elegant rhetoric. Although he has completed his term in office, his charismatic image and cautious yet authoritative communication style remain relevant in Indonesia's political landscape. The findings indicate that SBY’s charismatic leadership not only had an impact during his presidency but also serves as a model for stable, intellectual, and ethical political communication for current and future leaders.